PUBLIC ARCHITECTURE OF THE LATE ARCHAIC IN THE VALLEY OF FORTALEZA. REFLECTIONS ON EARLY COMPLEX COMPANIES IN THE NOR-CENTRAL COAST - Vega-Centeno Sara-Lafosse, Rafael (2004)
I present in this article the results of survey and mapping at sites with early monumental architecture in the Middle Fortaleza Valley. Architecture provisionally assigned to the Late Archaic period is analyzed, and some hypotheses on its development are proposed. The Fortaleza sites are then compared with other ones throughout the North Central Coast. I propose that the architectural complexes in this region seem to correspond to local-range sociopolitical entities, instead of large, regional polities. Finally, I conclude with some thoughts on new theoretical perspectives to understand the origins and development of such entities.